Study on the mechanism of Ginkgo seeds in treating bronchitis by network pharmacology - Wu, Tingting; Zhang, Lihu; Li, Dongdong; Wu, Tao; Jiang, Yan; Zhao, Linguo (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, with the global environmental deterioration and air pollution, the incidence of bronchitis has increased year by year, and the sales of anti-bronchitis drugs are growing rapidly, mainly due to the long treatment cycle and the difficulty of curing. Developing available traditional Chinese medicines with significant curative effect against bronchitis would be a promising strategy; for instance, Ginkgo seeds, as the fruit of natural plant ginkgo, has been used in ancient times to cure coughs. However, the detailed mechanism of curing cough has not been shown yet. Investigate the mechanism of Ginkgo seeds in the treatment of bronchitis by establishing a series of molecular networks including active ingredients-targets, proteins interactions, biological functions, pathway, and biological processes of targets. In this study, the main active ingredients of Ginkgo seeds and the potential targets related to bronchitis could be obtained by retrieving corresponding database. The molecular docking study between active molecules and protein targets was performed by Glide 6.6. Subsequently, a total of forty potential targets were manually selected. Based on this, the ingredients-target network was constructed using Cytoscape software, as well as proteins interactions network combing with the String database. Finally, the molecular biological function, metabolic pathway, and biological processes of these forty targets were analyzed by Clue GO plug-in. The results indicated that these protein targets were closely related to lipid transport, positive regulation of DNA replication, cAMP metabolic pathway, and other processes, which played a vital role in the treatment of bronchitis by mediating interleukin 17, fluid shear stress and atherosclerosis, asthma, renin secretion, p53, and other signaling pathways. Among these targets, the two protein ALB (Albumin) and DHRS2 (Dehydrogenase 2) can interact with compounds more frequently, and the top three compounds ranked by the docking scores were amentoflavone, (+)-catechin-5-O-glucoside, and liquiritin, implying that these compounds might be used for the treatment of bronchitis. It is obvious that the pharmacological effect of Ginkgo seeds on bronchitis displayed a characteristic of multi-components, multi-targets, and multi-pathways. Nevertheless, the two protein targets and three compounds derived from Ginkgo seeds could be further used for the explanation for Ginkgo seeds in curing bronchitis. This research can provide a scientific basis for studying on the anti-bronchitis mechanism of Ginkgo seeds.